Colonization of hospital water systems by Legionella pneumophila, Pseudomonas aeroginosa, and Acinetobacter in ICU wards of Tehran hospitals - Somayeh Yaslianifard; Ashraf Mohabati Mobarez; Bahram Fatolahzadeh; Mohammad Mehdi Feizabadi (Wolters Kluwer Medknow Publications, 2012)
Background: Nosocomial infection caused by non-Enterobacteriaceae gram negative bacteria (GNB-NE) is increasing in intensive care units (ICU). Aim: The objective of this study was to determine whether potable water in ICU wards at Tehran hospitals is contaminated with L. pneomophila, P. aeroginosa and Acinetobacter spp. Materials and Methods: A total of 52 water samples from shower bath and taps water in seven hospitals of Tehran were collected. The water sample concentrated by filtering through millipore cellulose filters and cultured on BCYE agar and tryptic soya agar media. The presence of Legionella pneumophila was confirmed by real time PCR assay using primers-probe designed for the mip gene. Results: Legionella pneumophila, Pseudomonas aeroginosa and Acinetobacter were isolated from 5 (9.6%), 6 (11.4%) and 1 (1.8%) of the hospital water systems, respectively. This study demonstrated the presence of Legionella, Pseudomonas and Acinetobacter in water system in ICU wards of different hospitals in Tehran. Conclusions: Hot water from shower heads could be a potential source of infection for Legionella pneumophila. Water was also proved to contain Pseudomonas aeruginonsa, the main GNB-NE causing nosocomila pneumonia at Tehran hospitals. Care should be taken concerning cleanliness and decontamination of water supplies at ICUs for pathogenic organisms.